2013
DOI: 10.1016/s0924-9338(13)75981-9
|View full text |Cite
|
Sign up to set email alerts
|

791 – Dual diagnosis of schizophrenia and substance abuse: the need for awareness

Abstract: Background:The dual diagnosis of substance abuse and severe mental illness has been proposed by some authors to highlight the high frequency of such association. Our objectif was to determine the prevalence of dual diagnosis among mentally ill patients and and particularly schizophrenic patients. as a secondary purpose, to describe the profile of patient at higher risk to develop dual diagnosis.Method:683 mentally ill patients were recruited from el Mamoura Psychiatric Hospital, they were assessed by the Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 0 publications
2
2
0
9
Order By: Relevance
“…Similar results were also found in other investigations as in the Picci et al [12], where the participants were aged 18-44, free or divorced and widowed, the same research by Rady et al [13] revealed that the majority of the sample (63%) was single, with low socio-economic and educational level. Also the national survey by Magidson et al [22], typically indicate that people with double diagnosis were more likely to be divorced / deprived, in the absence of a supportive environment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were also found in other investigations as in the Picci et al [12], where the participants were aged 18-44, free or divorced and widowed, the same research by Rady et al [13] revealed that the majority of the sample (63%) was single, with low socio-economic and educational level. Also the national survey by Magidson et al [22], typically indicate that people with double diagnosis were more likely to be divorced / deprived, in the absence of a supportive environment.…”
Section: Discussionsupporting
confidence: 88%
“…The low level of education in this research is supported by other European studies where the presence of dual diagnosis was higher in patients with low socio-economic and educational back-ground, usually with chronic education of less than 9 years [13,[30][31][32][33][34]. The majority of the sample included in the psychiatric unit was in the group of inactive (60.3%), with the main source of income for the pension or sickness benefit (66.7%).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, Rady, Salama, Elkholy, and Shawky (2013a, 2013b, 2013c, 2013d) showed that 57.32% of personality disorders patients, 17.71% of mood disorders patients, 17.42% of anxiety disorders patients and 16.67% of schizophrenic patients of a psychiatric hospital of Egypt suffered from dual diagnosis. It is often observed that patients with dual diagnosis present more than one mental disorder along with the substance use disorder (e.g., Ding, Yang, Cheng, Schiltz, summers, and Skinstad, 2011; Lechner et al, 2013) [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Μέζα ζε απηά ηα πιαίζηα, ε αλάγθε γηα έξεπλα ζην ζπγθεθξηκέλν ζέκα είλαη ζεκαληηθή. Ζ πξννπηηθή δηεξεχλεζεο ηεο δηπιήο δηάγλσζεο θαη ησλ ραξαθηεξηζηηθψλ ησλ αηφκσλ πνπ παξνπζηάδνπλ δηπιή δηάγλσζε, επηρεηξεί λα εμεγήζεη ηφζν ην πψο απηφ ην θαηλφκελν επεξεάδεη ην ζεξαπεπηηθφ απνηέιεζκα, ηελ πνξεία ηεο λφζνπ, ην αξηζκφ εηζαγσγψλ, φζν θαη ην πψο επεξεάδεη γεληθφηεξα ηελ ρξήζε Τπεξεζηψλ Φπρηθήο Τγείαο (Batalla et al, 2013;Picci et al, 2013;Rady Salama, Elkholy, & Shawky, 2013a;van Dijk, Koeter, Hijman, Kahn, & van den Brink, 2012;Wu et al, 2013;.…”
Section: πεξηγξαθή εκαζία θαη αλαγθαηόηεηα ηνπ δξεπλεηηθνύ πξνβιήκαηνοunclassified